A modified Delphi study towards developing a guideline to inform policy on fetal alcohol spectrum disorders in South Africa: a study protocol. Issue 4 (27th April 2018) - Adebiyi, Babatope O; Mukumbang, Ferdinand C; Okop, Kufre J; Beytell, Anna-Marie
Abstract : Introduction: Maternal alcohol consumption during pregnancy can result in mental and physical birth defects in individuals. These birth defects are usually described as fetal alcohol spectrum disorders (FASDs). With an estimated 183–259 per 1000 children born with FASDs, South Africa is identified to have the highest prevalence of FASDs in the world. Nevertheless, there is a lack of appropriate policies, guidelines and interventions addressing the issues around FASDs. This protocol outlines a proposed process for developing a guideline to inform policies on FASDs. Methods and analysis: This process will have three phases. Phase I will be carried out in three steps; we plan to conduct a document review of available policies on the prevention and management of FASDs and update the existing systematic review on FASDs interventions. The aim of the two reviews is to explore the availability and content of existing policies and global interventions on FASDs. In addition, we will conduct two exploratory qualitative studies to obtain the perspectives of various stakeholders on the existing or possible guidelines and policies for the management of FASDs and available interventions and services. In phase II, we will aggregate the findings of the previous phase to develop a prototype guideline. In phase III, using the developed prototype, we will apply the Delphi approach with experts on FASDs, soliciting their opinions on the nature and content of the proposed guidelines for policies. The information gathered will be used to modify the prototype to formulate a policy guideline on FASDs. The data will be analysed using thematic analysis and narrative synthesis. Ethics and dissemination: Ethical clearance has been obtained from the ethics committee of the university and governmental departments. The findings will be disseminated through publications and the guideline will be submitted to relevant departments.